Clinical and imaging characteristics of subacute combined degeneration complicated with white matter lesions in the brain: a report of five cases. (3rd April 2018) - Chen, Hao; Li, Hengyu; Li, Yuncheng; Jing, Jia; Raza, Hafiz Khuram; Zhang, Zuohui; Dong, Liguo; Ye, Xinchun; Hua, Fang; Cui, Guiyun
Abstract: Purpose: To report five cases of subacute combined degeneration (SCD) with brain involvement and explore its clinical and imaging characteristics. Methods: A retrospective study was performed on the clinical data and brain MRI of five patients with subacute combined degeneration with brain involvement (out of 107 cases with SCD in total). White matter lesions (WML) assessment was performed qualitatively using Fazekas scale score. Results: The main symptoms in four patients were weakness in both lower extremities and unstable walking (limb weakness in three patients, dizziness in three patients, and blurred vision in one patient). One patient had memory loss and cognitive dysfunction. The MMSE scale indicated mild dementia in one patient. On head MRI (Magnetic Resonance Imaging), multifocal and symmetrical high signals of T2WI and FLAIR were observed in the frontal lobe and periventricular white matter in four patients, while another patient showed preferential atrophy in frontal regions. Fazekas scale scores ranged from 1–6. Conclusion: Adult subacute combined degeneration seldom involves the brain. Multifocal and symmetrical high signal white matter lesions can be found on FLAIR and T2WI, as well as frontal atrophy on head MRI.